1H-magnetic resonance spectroscopy and its role in predicting neurodevelopmental impairment in preterm neonates: A systematic review. Issue 6 (December 2022) - Laccetta, Gianluigi; De Nardo, Maria Chiara; Cellitti, Raffaella; Angeloni, Ugo; Terrin, Gianluca
To assess the diagnostic utility of proton ( 1 H) magnetic resonance spectroscopy in early diagnosis of neurodevelopmental impairment in preterm newborns. Systematic review performed in compliance with the PRISMA statements. Eligible articles were searched in MEDLINE, Scopus, and ISI Web of Science databases using the following medical subject headings and terms: "magnetic resonance spectroscopy, " "infant, " and "newborn." Studies of any design published until 20 December 2021 and fulfilling the following criteria were selected: (1) studies including newborns with gestational age at birth <37 weeks which underwent at least one 1H-MRS scan within 52 weeks' postmenstrual age and neurodevelopmental assessment within 4 years of age; (2) studies in which preterm newborns with congenital infections, genetic disorders, and brain congenital anomalies were clearly excluded. Data regarding the relationship between metabolite ratios in basal ganglia, thalamus, and white matter, and neurodevelopment were analysed. The quality assessment of included studies was performed according to the criteria from the QUADAS-2. N-acetylaspartate (NAA)/choline (Cho) was the most studied metabolite ratio. Lower NAA/Cho ratio in basal ganglia and thalamus was associated with adverse motor, cognitive, and language outcomes, and worse global neurodevelopment. Lower NAA/Cho ratio in white matter was associated with cognitive impairment. However, some associations came from single studies or were discordant among studies. The quality of included studies was low. 1 H-MRS could be a promising tool for early diagnosis of neurodevelopmental impairment. However, further studies of good quality are needed to define the relationship between metabolite ratios and neurodevelopment.